Internal forces that influnces employees' change readiness : a study on One Store in Malaysia - Cheong, Kah Seng; Chong, Ruijing; Lim, Shi Sui; Ng, Soo Yen; Wong, Kok Hong (2011)
The study is conducted to examine the internal forces that influence employee change readiness that based on a retailer store in Malaysia. It is important to prepare the employees to be ready for the change to successfully implement the change. This study is to focus on how each factors that influence the employees’ readiness to change and to explore the determinants of the factors that will lead to their readiness to change. Besides that, the relationship between the variables of employees’ readiness, organisational commitment, communication, leadership and self-efficacy will defined the action that should be taken to prevent chaos and to prepare the employees for the change. The result show statistically significant positive relationship for all variables which include organisational commitment, communication, leadership and self-efficacy. Therefore provides empirical data to support theoretical models for this research study.